The Relationship Between Knowledge About Kangaroo Mother Care (Kmc) Among Mothers and Increased Weight of Low Birth Weight (Lbw) Babies in the Neonate Intensive Care Room of the Mayapada Hospital Jakarta Selatan - Indriani, Nuke Tri; Lase, Arozamati W; Ria, Rome Tao Toba Muara; Buka, Sicily Prima Yanuaria; Meilina, Herlina (Journal of World Future Medicine, Health and Nursing, 2025)
One of the main causes of infant mortality is low birth weight babies. Low birth weight babies are high risk babies and are susceptible to various problems such as the risk of respiratory infections, low blood sugar levels (hypoglycemia), eating disorders, too many red blood cells and the risk of experiencing hypothermia. Hypothermia in babies with low birth weight is caused by very thin subcutaneous fat so it is influenced by environmental temperature. In general, babies with low birth weight must be treated with an incubator or using the KMC method so that their body temperature is maintained. This study aims to determine the relationship between knowledge of the Kangaroo Mother Care (KMC) method among mothers and the increase in Low Birth Weight (LBW) Babies in the NICU Room at Mayapada Hospital, South Jakarta. This research is quantitative using a correlative analytical descriptive design with a cross sectional approach. Conclusion: shows that there is a significant relationship between knowledge about the Kangaroo Mother Care (KMC) Method in mothers and the increase in Low Birth Weight (LBW) in the NICU room at Mayapada Hospital, South Jakarta.